Kematian Eksistensi Manusia dalam Sonnet 73 karya William Shakespeare: Death of Human Existence in Sonnet 73 William Shakespeare Work - Ummu Fatimah Ria Lestari (Balai Bahasa Provinsi Papua, 2022)
Sonnet 73 by William Shakespeare is an interesting sonnet to discuss. The most basic reason for studying this sonnet is because it reveals the phenomenon of death as part of human existence. In addition, to the researcher's knowledge, the phenomenon of human death in this sonnet has never been studied from an existential perspective. The phenomenon of death contained in this sonnet will be discussed through an existential perspective so that it will bring up interpretations and analysis results of this poem in various perspectives. Sartre (2002:73) in his existentialist view argues that there is no reality, except in action. Man is nothing but what his life reveals. The concept of death understood in existentialism is the death of human existence. The death of this existence can also mean the human condition when he is in a state of despair, anxiety arises, and has a sense of nothingness.